Synthesis and Biological Evaluation of Acetylcholinesterase Inhibitor Macakurzin C and Its Derivatives - Baek, Seung-Hoon; Jang, Hongjun; Kim, Hyoungsu (Synlett, 2015)
The derivatives of macakurzin C containing a modified D ring and protected C(3)/C(5)-hydroxyl groups were synthesized and their in vitro AChE inhibitory activity and neurotoxicity were evaluated to identify the structural requirements for the activities. The results indicated that C(3)-benzyl-protected derivative has a more potent AChE inhibitory activity (IC50, 2.6 μM) and a less neurotoxicity (GI50, >100 μM) than synthetic macakurzin C (IC50, 9.1 μM; GI50, 16.6 μM).
Keywords: natural products; macakurzin C; aromatic Claisen rearrangement; acetylcholinesterase inhibitors; tandem reaction